Properties of fly ashes from thermal power stations in relation to use as soil amendments - Thien, Le Van; Chau, Ngo Thi Tuong; Hong, Le Thi Tham; Trang, Nguyen Thu; Futamata, Hiroyuki (Penerbit Universiti Kebangsaan Malaysia, 2019)
Recycling fly ashes is a good alternative to disposal with the significant economic and environmental benefits. Characterization of fly ashes can be helpful to evaluate their use potentials. This study aimed to investigate the physical, chemical and mineralogical properties of fly ashes from five thermal power stations in Northern Vietnam in relation to use as sandy soil amendments. The results showed that the fly ashes were dominated by silt-sized and spherical particles and had low bulk densities. There was almost not significant difference in the surface charges among the fly ashes; however, their surface areas varied widely. The fly ashes were alkaline. The electrical conductivity and cation exchange capacity in the fly ashes were higher than those in the sandy soil. The concentrations of extractable K, P, Ca2+ and Mg2+ in the fly ashes were higher compared with the sandy soil. The major matrix elements in the fly ashes were Si, Al, and Fe together with significant percentages of K, Mg, Ca and Ti. Quartz was the most predominant mineral present in the fly ashes. Several radioactive elements were found in the fly ashes with very low concentrations. The potential to release trace elements from the fly ashes was below the regulatory guidelines. The amendment of fly ashes to the sandy soil led to the substantial decrease in the hydraulic conductivity but the increase in the plant-available water contents of the sandy soil. It is recommended to use the fly ashes as soil amendments for sandy soil amelioration.